The Dispersion of Bonus Payments within and between Firms - Christian Grund; Tanja Hofmann (Institute of Labor Economics (IZA), 2017)
We explore the dispersion of bonus payments of managers within and between five large firms from the German chemical sector. We use data from a yearly salary survey in these firms during the observation period 2008 to 2013. Bonus payments account for 20 percent of base salaries on average. Both the amount and the dispersion of bonus-to-base ratios differ across firms. We disentangle the dispersion between and within the levels of firms' hierarchies. Revealed differences are consistent with differences in firms' value statements.
Keywords: J31; J33; M52; 330; bonus payments; bonus to base rate; firm differences; pay policies; wage dispersion